STRATEGY OF THE KOMISI PEMILIHAN UMUM (KPU) IN INCREASING THE PARTICIPATION OF DISABILITIES VOTERS IN THE 2024 ELECTIONS IN THE CITY OF SUKABUMI - Abdullah, Abdullah; Basori, Yana Fajar F.Y.; Purwanti, Dian (DIA: Jurnal Administrasi Publik, 2025)
The purpose of this study was to determine how the strategy of the Komisi Pemilihan Umum of Sukabumi City to increase voter participation with disabilities in the upcoming 2024 elections. The research method used is qualitative, the informant settings that researchers determine in this study are the Chairperson of the Sukabumi City Komisi Pemilihan Umum, the Coordinator of the Socialization Division, Voter Education, Community Participation, and Human Resources, Persons with Disabilities of Gunung Puyuh District. The data collection techniques used were observation, interview, and documentation, and the data validation used was triangulation technique. The results of this study show that the Sukabumi KPU has implemented the principles of strategic planning and action selection in accordance with the theory proposed by Salusu (2015). The implementation of this effective strategy leads to more directed and successful efforts in increasing voter participation with disabilities in the 2024 General Election in Sukabumi City.